2005
DOI: 10.1186/1743-7075-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Glucocorticoids are stress hormones that modulate a large number of physiological actions involved in metabolic, inflammatory, cardiovascular and behavioral processes. The molecular mechanisms and the physiological effects of glucocorticoids have been extensively studied. However, the involvement of glucocorticoid action in the etiology of the Metabolic Syndrome has not been well appreciated. Recently, accumulating clinical evidence and animal genetics studies have attracted growing interest in the role of glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(85 citation statements)
references
References 191 publications
6
76
0
2
Order By: Relevance
“…This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23]. Glucocorticoid excess has been linked to clinical observations associated with the metabolic syndrome such as central obesity, hypertension, hyperlipidaemia and glucose intolerance [27]. These clinical features associated with glucocorticoids are similar to the phenotypic traits that are programmed in utero following feeding of LP diets in rat pregnancy [9,18].…”
Section: Discussionmentioning
confidence: 94%
“…This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23]. Glucocorticoid excess has been linked to clinical observations associated with the metabolic syndrome such as central obesity, hypertension, hyperlipidaemia and glucose intolerance [27]. These clinical features associated with glucocorticoids are similar to the phenotypic traits that are programmed in utero following feeding of LP diets in rat pregnancy [9,18].…”
Section: Discussionmentioning
confidence: 94%
“…This fact is relevant, taking into account that we studied strictly controlled normoweight neonates. It has been suggested that insulin resistance accompanied by hypercortisolaemia may be important in the development of metabolic syndrome in adults [34].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Numerous studies have implicated glucocorticoid action in the regulation of hepatic gluconeogenesis and lipogenesis, glucose uptake and lipid oxidation in skeletal muscle, and the production of angiotensinogen. [6][7][8] Patients with Cushing's syndrome have increased glucocorticoid exposure and exhibit similar symptoms compared with those with metabolic syndrome, including insulin resistance, high adiposity, dyslipidemia and hypertension. [9] These metabolic abnormities in Cushing's syndrome could be improved to a certain degree by decreasing the excessive glucocorticoid action through surgery or glucocorticoid receptor antagonist treatment.…”
Section: Introductionmentioning
confidence: 99%